2019
DOI: 10.1080/15592294.2019.1666652
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C in combination with inhibition of mutant IDH1 synergistically activates TET enzymes and epigenetically modulates gene silencing in colon cancer cells

Abstract: (2020) Vitamin C in combination with inhibition of mutant IDH1 synergistically activates TET enzymes and epigenetically modulates gene silencing in colon cancer cells,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 68 publications
(85 reference statements)
0
14
0
Order By: Relevance
“…Of interest, 2-phosphate L-ascorbic acid is a compound that is stable in cell culture and does not induce the production of extracellular H 2 O 2 , allowing to study only the activity of vitamin C as enzymatic regulator [ 108 , 109 ]. IDH1/2 mutations are also detected in solid tumors (e.g., glioma, colorectal, breast, renal cancers) and in an IDH1 mutated colorectal cancer cell line, treatment with vitamin C synergized with an IHD1 inhibitor by rescuing TET activity [ 110 ].…”
Section: Mechanisms Of Vitamin C Anticancer Actionmentioning
confidence: 99%
“…Of interest, 2-phosphate L-ascorbic acid is a compound that is stable in cell culture and does not induce the production of extracellular H 2 O 2 , allowing to study only the activity of vitamin C as enzymatic regulator [ 108 , 109 ]. IDH1/2 mutations are also detected in solid tumors (e.g., glioma, colorectal, breast, renal cancers) and in an IDH1 mutated colorectal cancer cell line, treatment with vitamin C synergized with an IHD1 inhibitor by rescuing TET activity [ 110 ].…”
Section: Mechanisms Of Vitamin C Anticancer Actionmentioning
confidence: 99%
“…Low-grade primary gliomas commonly harbor IDH mutations that persist during progression to secondary GBM ( 24 ). In vitro , ascorbate was able to circumventing competitive inhibition by 2-HG in colon cancer and HOXA9-immortalized mouse bone marrow cells with IDH1 R132H mutations ( 206 , 207 ). One in vitro study reported the effects of ascorbate on epigenetic marks in LN229 glioma cells, showing increased TET3 mRNA expression, as well as increased 5-hmC, but these cells did not harbor an IDH mutation ( 64 ).…”
Section: Substrate and Cofactor Requirements Of 2-ogddsmentioning
confidence: 99%
“…Maintenance of pluripotency of stem cells [71,72] Differentiation [73,74] TET2 Reprogramming [75][76][77][78][79] Diabetic skin diseases [80] Coronary heart disease [81] NK cells maturation [34] Allergic rhinitis [35] TET3 Demethylate the genome of the fertilized zygote to allow it to grow into a fully developed organism [82] Neuron development and maturation [83] Neuron cells repair and recovery [84] Neural progenitor cells specification/cellular identity/Proliferation/Differentiation [36,85,86] TET3-deficiency syndrome and Mendelian inheritance patterns [86] Bone marrow hypoxia and development of Xenopus tadpole brain [87,88] TET1/TET2/TET3 Critical for brain functions [85,86,[89][90][91] Mutations or changes are associated with/the cause of cognitive deficits in human [36] Initially, it was accepted that TET1 was a direct or indirect tumor repressor [92]. Indeed, repression of TET1 expression or aberrant subcellular localization of TET1 in gastric cancer (GC) tissues led to carcinogenesis associated with significantly lower 5-hmC, suggesting the crucial role of TET1 as a cancer repressor [93].…”
Section: Tet1mentioning
confidence: 99%